Lucy, Lucia, and Locke - Halmi, Nicholas (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractMadness may remain silent in fiction, but not in opera. In giving voice to the madness of Lucia in Donizetti’s Lucia di Lammermoor, his adaptation of Scott’s The Bride of Lammermoor, librettist Salvadore Cammarano departs not only from the novel’s coy supernaturalism, which permit’s Lucy’s otherwise inexplicable madness to be attributed to unseen forces beyond her control, but also from the concept of reality implied in that supernaturalism. Whereas Lucy’s madness seems to consist in a demonic possession, Lucia’s consists in the creation of a subjective reality that is consistent with itself but not with the events enacted on stage. Thus the concept of reality implied in the opera—a reality divided between what is inside and what is outside the mind—is essentially Lockean.